Chinese calligraphy as cultural mediation: a cultural-historical activity theory perspective on therapeutic practice for neuropsychiatric symptoms - Chu, Kuan-Yu (Frontiers in Psychiatry, 2025)
Chinese calligraphy therapy (CCT) represents an emerging culturally mediated intervention demonstrating significant therapeutic potential for neuropsychiatric symptoms including anxiety, depression, schizophrenia, and cognitive impairment. This perspective integrates Cultural-Historical Activity Theory (CHAT) to elucidate the psychosocial mechanisms underlying CCT’s effectiveness, synthesizing meta-analytic evidence that demonstrates standardized mean differences of -0.17 for psychosis reduction and significant improvements in anxiety symptoms. The framework reveals how traditional calligraphic practice functions as a mediational tool, facilitating psychological transformation through cultural mediation, community participation, and zone of proximal development activation. Current research indicates CCT’s capacity to enhance neural efficiency, promote flow states, and improve cognitive function in diverse populations. This perspective advocates for systematic integration of culturally authentic practices within evidence-based mental healthcare, proposing future directions including longitudinal studies, cross-cultural validation, and community-based implementation. The analysis contributes to understanding how traditional therapeutic modalities can address contemporary mental health challenges through theoretically grounded, culturally responsive approaches.